Annie Proulx’s Imaginative Leap: Constructing Gay Masculinity in “Brokeback Mountain” - Hart, Kylo-Patrick R. (Text Matters: A Journal of Literature, Theory and Culture, 2012)
Non-heterosexual men have long existed on the social and cultural margins. Gay and bisexual male characters in literature, too, have done so for many generations. This essay explores the construction of gay masculinity in the short story “Brokeback Mountain” in relation to the “imaginative leap” that its author, Annie Proulx, undertook in order to conceptualize and represent this noteworthy form of marginalized otherness. It demonstrates that, despite the story’s various refreshing elements, “Brokeback Mountain” ultimately relies far too extensively on the logic of melodrama when telling the tale of Ennis del Mar and Jack Twist, who fall in love in 1963 and continue their sexual relationship over the course of two decades. As a result, this story ends up positioning its two queer protagonists as enemies of the patriarchal social order and the larger society within which it so comfortably exists, implicitly perpetuating both heterosexism and homophobia as it does its cultural work.